Potential Application of Selected Sulfur-Oxidizing Bacteria and Different Sources of Sulfur in Plant Growth Promotion under Different Moisture Conditions. Issue 6 (25th March 2020) - Pourbabaee, Ahmad Ali; Koohbori Dinekaboodi, Shirin; Seyed Hosseini, Hossein Mir; Alikhani, Hossein Ali; Emami, Somayeh
ABSTRACT: This study aimed to investigate the combined effect of native sulfur-oxidizing bacteria and different sources of sulfur on pH, electrical conductivity, sulfate content in soil, plant growth indices and sulfate uptake by maize under different moisture conditions. A native sulfur-oxidizing bacteria was isolated and identified based on phenotypic characteristics and 16s rDNA sequencing. In this regard, a factorial experiment was conducted in a completely randomized design including Thiobacillus bacteria, sulfur sources, moisture and incubation time as experiment's factors with three replications. Bacteria in two levels (with and without bacterial isolate), sulfur in three forms (elemental sulfur, granular sulfur and without sulfur), and moisture content in three levels (100%, 75% and 50% of field capacity) were considered. Results obtained from incubation experiment showed that the treatments effect on pH changes, electrical conductivity and the amount of sulfate ion were significant in 1% level and the highest pH changes and sulfur oxidation was related to BS 100% field capacity (inoculated and fertilized with elemental sulfur) treatment in second week. About greenhouse experiment, application of 570 mg sulfur per kg in the form of elemental sulfur and bacterial inoculum significantly increased stem diameter, plant height, shoot weight and sulfate uptake by maize plant. Inoculation of Thiobacillus along with elemental sulfur increases the oxidation of elemental sulfur resulting in increased nutrients availability in soil, consequently increased plant growth.